Sintering investigations of a UO2-PuO2 powder synthesized using the freeze-granulation route. (September 2020) - Le Guellec, Marion; Lebreton, Florent; Ramond, Laure; Ndiaye, Abibatou; Gervais, Thierry; Bernard-Granger, Guillaume
Abstract: Sintering investigations of a UO2 -PuO2 powder, integrating 11 wt% of PuO2 and synthesized by freeze-granulation, were completed at temperatures up to 1700°C, in an atmosphere of Ar/4 vol% H2 and 1200 vpm H2 O. Analyzing the "grain size versus relative density" trajectory enabled to propose that densification was controlled by volume diffusion and grain growth by the grain boundaries. An activation energy around 630 kJ/mol was obtained for densification, which was close to the value reported for volume diffusion of plutonium cations in U1-x Pux O2 polycrystals. The sintered microstructure appeared homogeneous regarding the plutonium and uranium cations distribution. Graphical abstract: Image, graphical abstract